2017
DOI: 10.3892/ijo.2017.3863
|View full text |Cite
|
Sign up to set email alerts
|

PIM1 knockdown inhibits cell proliferation and invasion of mesothelioma cells

Abstract: Malignant mesothelioma is a major asbestos-related cancer with prolonged time lapse from the first exposure of asbestos to the development of mesothelioma. Most of mesothelioma patients show very poor prognosis, thus, an urgent improvement of its treatment is required by development of novel therapeutic strategies. RNA interference (RNAi) is a powerful tool in post-genomic research and cancer therapy through inhibition of gene expression. In the present study, we analyzed the function of PIM1 on mesothelioma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Consistent with our expectations, we found that LMP1-induced increase in Pim1 expression indeed promoted proliferation of NPC cells. Our results were consistent with other lab findings that proved high Pim1 expression enhanced cancerous cell growth 1,3032…”
Section: Discussionsupporting
confidence: 94%
“…Consistent with our expectations, we found that LMP1-induced increase in Pim1 expression indeed promoted proliferation of NPC cells. Our results were consistent with other lab findings that proved high Pim1 expression enhanced cancerous cell growth 1,3032…”
Section: Discussionsupporting
confidence: 94%
“…Johnson et al (22) found that a miR-137 mimic inhibited the proliferation, invasion, and migration of mesothelioma cells, and Williams et al (23) found that miR-13 reduced proliferation, and increased apoptosis and necrosis of mesothelioma cells by downregulating MCL1. Further, we demonstrated previously that miR-1 and miR-214 inhibited mesothelioma cell progression by suppressing PIM1 (11,24), and miR-182 and miR-183 promoted mesothelioma cell progression by suppressing FOXO1 (25).…”
Section: Discussionsupporting
confidence: 57%
“…Pim1 is overexpressed in various tumours such as breast cancer and prostate cancer and promotes tumour progression by promoting cell proliferation, survival and inhibition of apoptosis . Moreover, Pim1 promotes cancer cells growth by enhancing the Warburg effect and promotes epithelial‐mesenchymal transition and oncogenesis . Therefore, miR‐24‐2 is likely to play a carcinogenic role by promoting the expression and function of Pim1 in liver cancer.…”
Section: Discussionmentioning
confidence: 99%